Behaviour of grout-filled double-skin tubular steel stub-columns: Numerical modelling and design considerations. (October 2020) - Tziavos, Nikolaos I.; Gkantou, Michaela; Theofanous, Marios; Dirar, Samir; Baniotopoulos, Charalampos
Highlights: Numerical study on the performance of circular grout-filled double skin stub-columns. Influence of hollow ratio for varying cross sections on the compressive resistance. Assessment of codified methods and analytical models for strength prediction. Abstract: The use of grout-filled double-skin tubular (GFDST) sections in civil, bridge and offshore engineering applications is rapidly increasing. The design of such composite members is not directly covered by design codes, despite recent research studies investigating their performance, proposing design equations or modifying existing codified methods. Aiming to extend the available pool of structural performance data, the current study reports the results of an extensive numerical investigation on GFDST stub-columns. Finite element (FE) models, are developed and validated against published test data. A parametric investigation is conducted to evaluate the effect of key parameters, including cross-sectional slenderness, hollow ratio and the effect of concrete infill on the capacity of GFDST members. The numerically obtained load capacities along with collated test data are utilised to assess the applicability of design strength predictions based on European Code (EC4), the American Concrete Institute (ACI) and the analytical models proposed by Han et al. and Yu et al. Overall, the modified Yu et al. provided strength predictions with low scatter, whereas ACI yielded overly conservative predictions particularly for smaller hollow ratios.